Perancangan Database Peminjaman dan Pengembalian Buku di Perpustakaan SMKN 1 Padang Panjang Berbasis Microsoft Access - Wahyuni, Putri; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
Database design aims to create a database service borrowing and returning books in Library SMK Padang Panjang 1 based on Microsoft Access. The method used is the method of observation that is by studying the manual system previously used by the library. Literature is to look for books, papers, and articles from the internet that will be used to design a new system that will be created. The database design activity is as follows: First, create a table that consists of a group of students table, group table book, group transactions table and transaction table book group; second, create queries relationship between the book table and transaction table book; Third, create a form design that student data form, the form book data, and the form of the transaction; Fourth, create a report and report student book; fifth, to make the main menu database. With the database is expected to help the librarian in the service book borrowing and return quickly. Librarians can also present the data reported borrowing and returning books appropriately and accurately. Keywords: database; borrowing; repayment